Bolavoli : Latihan Ball Drop Drill untuk Meningkatkan Keterampilan Pasing Bawah - Sari, Eka Novita; Irwanto, Edi; Triaiditya, Bayu Septa Martaviano; Santoso, Danang Ari (SPRINTER: Jurnal Ilmu Olahraga, 2024)
This research aims to determine the effect of ball drop drill training on improving the bottom passing skills of female volleyball athletes at SMAN 1 Tegaldlimo.  This research uses experimental methods. The sample in this research consisted of 8 students. The technique for collecting data on fitting skills uses AAHPERD TEST tests and measurements. The data analysis technique uses SPSS 25. The results of the research show that there is a significant increase in bottom fitting skills by using ball drop drill training at 0.001 < 0.05. This means that this exercise can be used to improve volleyball bottom passing skills.